Multi-crystallization enhancer for concrete waterproofing by pore blocking. (22nd February 2021) - Al-Rashed, Radi; Al-Jabari, Maher
Highlights: MCE combines the mechanism of hygroscopicity, hydrophilicity and hydrophobicity. MCE reduces porosity and water penetration by a dynamic crystal growth mechanism. MCE enhances workability, compressive strength and abrasion resistance. MCE enhances concrete durability. Abstract: Concrete porosity and moisture penetration create several durability problems. The recent industrial solutions are based on the use of integral waterproofing materials. This paper responds to the need for developing an efficient pore blocking waterproofing aqueous solution that is added with mixing water at the time of batching, without requiring further work after curing. The paper presents an innovative multi-crystallization enhancer (MCE) which combines hygroscopic and hydrophilic crystals with a hydrophobic characteristic, all integrate in the concrete structure. The performance of the MCE system was investigated experimentally using two types of prescribed mix designs of Illinois Department of Transportation (IDOT), including plain concrete and modified concrete using fly ash. The investigated parameters included permeable pores, relative humidity in pores, water absorption, moisture emission, density, compressive strength, abrasion resistance and workability. Experiments were performed according to ASTM procedures. Test results showed that MCE reduced the porosity and the permeability of concrete. MCE also reduced the humidity within pores and actively managed free moisture through its dynamic crystal growth mechanism. Furthermore, MCE increased the workability, the compressive strength and the abrasion resistance. MCE is an effective solution to concrete durability problems.